HUBUNGAN ANTARA KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM KERJA GURU DENGAN KINERJA GURUDI SMKFK DAN SMAK2 PENABUR JAKARTA - Fransisca Arlianti; Witarsa Tambunan (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2015)
This study aims to determine the correlation of the leadership of principal school and teacher’s work climate with the teacher’s performance at SMKFK and SMAK2 PENABUR Jakarta, with the leadership of principal school (X1) andteacher’s work climate (X2) as independent variable, and teacher’s performance (Y) as dependent variable.This study was conducted in SMKFK dan SMAK2 PENABUR Jakarta at Yayasan BPK PENABURfrom November to December2014. The research method is used for correlational research method. Data collection techniques use a questionnaire with Likert scale which measures 1-4. This research is represented by 61 of SMKFK and SMAK2 PENABUR Jakarta as respondents. The techniques used are a simple correlation analysis, multiple correlation and multiple regression at alpha significance level at 0.05.This study concluded that Hypothesis 1 shows a positive and significant relationship between the leadership of principal school and teacher’s performance with a correlation coeficient of ry1 = 0.986, linear regression equation Y = -33.757 + 1.145X1, tcount = 46.156 is greater than ttable = 1.671 andthe coefficient of determination r2 = 0.973. The coefficient of determintation value by 0.973 to show that the leadership of principal school contributed for correlation with teacher’s performance variable by 97,3%. Hypothesis 2 shows a positive and significant relationship between teacher’s work climate and teacher’s performance with a correlation coeficient of ry2 = 0.978, linear regression equation Y = -19.698 = 1.103X2, tcount = 36.252is greaterthan ttable = 1.671 andthe coefficient of determination r2 = 0.957. The coefficient of determintation value by 0.957 to show that teacher’s work climate contributed for correlation with teacher’s performance variable by 95,7 %. Hypothesis 3 shows a positive and significant relationship the leadership of principal school andteacher’s work climate simultaneously and teacher’s performance with a correlation coeficient of ry12 = 0.988, linear regression equation Y = -30.950 + 0.846X1 + 0.296X2, Fcount = 1151.751 is greaterthan Ftable= 3.16andthe coefficient of determination r2 = 0.975. The coefficient of determintation value by 0.975 to show that the leadership of principal school and teacher’s work climate contributed for correlation with teacher’s performance variable by 97,5 %.From the research results it can be concluded that the teacher’s performance at SMKFK and SMAK2 PENABURJakarta can be enchanced by improving the leadership of principal school and teacher’s work climate. Keywords : leadership of principal school, teacher’s work climateand Performance.